2016
DOI: 10.1177/1062860616651715
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Collaborative Team Care Model for Effective Insulin Use in an Academic Medical Center Primary Care Network

Abstract: Improving glycemic control across a primary care diabetes population is challenging. This article describes the development, implementation, and outcomes of the Diabetes Care Collaborative Model (DCCM), a collaborative team care process focused on promoting effective insulin use targeting patients with hyperglycemia in a patient-centered medical home model. After a pilot, the DCCM was implemented in 18 primary care practices affiliated with an academic medical center. Its implementation was associated with imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…[7] In brief, the program had the following core elements, shared by all practices: 1) A physician leader for support of the project, 2) A nurse (or nurse practitioner) diabetes champion who managed a population health diabetes registry, served as a single point of contact for patients, and coordinated diabetes management plans with the patient’s primary care physician and specialists, and 3) An assigned dietitian who accommodated and expedited referrals for nutrition counseling. [7] The diabetes champions used management protocols that specifically incorporated motivational interviewing techniques, scheduled ‘check-ins’ that were not tied to a clinic visit, and evidence-based protocols for insulin initiation and titration. [7] Implementation varied across clinics in two main ways—whether or not the dietitian was located on site, and whether the practice added other members of the practice to their core care team, such as medical assistants or front desk staff.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[7] In brief, the program had the following core elements, shared by all practices: 1) A physician leader for support of the project, 2) A nurse (or nurse practitioner) diabetes champion who managed a population health diabetes registry, served as a single point of contact for patients, and coordinated diabetes management plans with the patient’s primary care physician and specialists, and 3) An assigned dietitian who accommodated and expedited referrals for nutrition counseling. [7] The diabetes champions used management protocols that specifically incorporated motivational interviewing techniques, scheduled ‘check-ins’ that were not tied to a clinic visit, and evidence-based protocols for insulin initiation and titration. [7] Implementation varied across clinics in two main ways—whether or not the dietitian was located on site, and whether the practice added other members of the practice to their core care team, such as medical assistants or front desk staff.…”
Section: Methodsmentioning
confidence: 99%
“…Our academic medical center implemented a diabetes team care model within 20 primary care practices that were part of our practice-based research network between 2012 and 2014. [7] The model shifted the focus of diabetes care from a model that centered on the doctor-patient relationship with referrals to certified diabetes educators and dietitians as needed, to one that emphasized more protocolized, multidisciplinary care involving practice-based nurses and dietitians, embedded locally in clinics. [7] An evaluation of the model found significant improvement in glycemic control for patients with hemoglobin A1c > 9.0%.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Eisenstat et al (155) primarily addressing insulin use, patients with prediabetes and T2D were followed by a coordinated team in a network of primary care physicians, using evidencebased recommendations addressing medical, behavioral, and nutrition/lifestyle components. Certain factors were identified that facilitated care: diverse stakeholder engagement and buy-in with the theoretical basis of the model, institutional alignment of priorities, and credits for participation and implementation (155). The close integration of pharmacists can also improve adherence factors in the care model (156).…”
Section: Dysglycemia-based Chronic Disease-a New Multimorbidity T2d Mmentioning
confidence: 99%